2017
DOI: 10.14429/dsj.67.10290
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Nitro-aromatic Compound in Soil and Sand using Time Gated Raman Spectroscopy

Abstract: Laser based time-gated Raman Spectroscopy experiments for detection and identification of nitro-aromatic sample which premixed with soil and sand in different concentrations are conducted. A back-scattered stand-off Raman spectroscopy set-up using a frequency double Nd:YAG pulsed laser (532 nm, 8 ns, 10 Hz) was employed to evaluate samples made up of standard nitro-aromatic compounds, p-nitro Benzoic acid (PNBA) premixed with soil and sand at different concentrations. A sensitive ICCD detector was used to capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The band at 3067 cm −1 can be associated with a symmetric stretching mode of C-H vibrations in benzene rings [ 51 , 52 ]. In the Raman spectra of benzoic acid, these vibrations appeared as the band with a maximum at 3085 cm −1 [ 53 ]. The difference between positions of the C-H peak in benzene (3067 cm −1 ) and benzoic acid (3085 cm −1 ) are explained by the effect of the substitute—carboxylic group.…”
Section: Resultsmentioning
confidence: 99%
“…The band at 3067 cm −1 can be associated with a symmetric stretching mode of C-H vibrations in benzene rings [ 51 , 52 ]. In the Raman spectra of benzoic acid, these vibrations appeared as the band with a maximum at 3085 cm −1 [ 53 ]. The difference between positions of the C-H peak in benzene (3067 cm −1 ) and benzoic acid (3085 cm −1 ) are explained by the effect of the substitute—carboxylic group.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a number of studies have been published that highlight the potential of Raman-based techniques for this role. Much of this work has centered on time-gated Raman for stand-off detection, which is discussed in a later section, and spatially-offset Raman spectroscopy (SORS); however, surface-enhanced Raman spectroscopy (SERS) has also been investigated, alongside other techniques. …”
Section: Applications Of Raman Scattering-based Techniques To Defense...mentioning
confidence: 99%
“…The ability to gate the collection of signal allows this approach to mitigate some of the fluorescent signal, which takes place over a longer time scale than the very rapid Raman scattering process, as well as exclude interference from daylight and atmospheric gases, like N 2 and O 2 , which would otherwise contribute to the detected signal to a measurable extent. Several studies have reported on this technique in the last 2 years, detecting explosive materials at distances from 50 cm to over 1 mile ,, as well as on a range of materials, such as soil, wood, and grass. , The ability to detect samples of interest in these kinds of materials is a vital component of Raman’s development into a viable tool for security applications, as real-world samples are often contaminated or on less-than-ideal surfaces.…”
Section: Stand-off and Robotic Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rising terrorist activities in worldwide have urged for the development of modern and easily transportable fully automated detection systems for rapid and reliable standoff detection and identification of almost all kind of explosives and harmful chemicals in real field scenarios [1][2][3][4][5][6][7][8] . In some scenarios like airports, metro stations, railway stations, markets and shopping malls, remote explosives detection techniques can be used in which the person investigating suspicious materials maintains a safe distance from the object being screened.…”
Section: Introductionmentioning
confidence: 99%